Corporate Responsibilities for Access to Medicines - Leisinger, Klaus M. (Journal of business ethics, 2009)
Today there is a growing wave of demands being placed upon the pharmaceutical industry to contribute to improved access to medicines for poor patients in the developing countries.1 This article aims to contribute to the development of a systematic approach and broad consensus about shared benchmarks for good corporate practices in this area. A consensus corridor on what constitutes an appropriate portfolio of␣corporate responsibilities for access to medicines – especially under conditions of ‘failing states’ and ‘market failure’2 – is not only in the interest of the world’s poor, but also of corporations that want to contribute to the solution of one of the most significant social problems of our time.